National Survey of 4th and 5th Grade Science Education Teachers: Insights Into Instruction and Inclusion of Students With Disabilities - Therrien, William J.; Wong, Vivian C.; Chen, Ling; Taylor, Christina M.; Chiu, Jennifer L.; Gonçalves, Bruna; Liu, Qing; Cook, Bryan G.; Doabler, Christian T.; Swanson, Elizabeth; Brame, Priscilla B.; Budin, Shannon; et al. (Science education (Salem, Mass.), 2025)
Elementary science education, particularly in the 4th and 5th grades, is essential for setting the foundation for lifelong science learning, fostering critical thinking, and preparing students for success in science, technology, engineering, and mathematics (STEM) fields. This stage is especially critical for students with disabilities, as achievement gaps between them and their peers emerge during elementary school. Despite this importance, little is known about how science is taught in elementary classrooms during these critical years, particularly for students with disabilities. To address this gap, we surveyed teachers from a nationally representative sample of U.S. schools to examine elementary science education, including instructional practices, allocation of time, and the inclusion and support of students with disabilities. Our findings reveal that limited instructional time is allocated to science, with significant variability across classrooms. The amount of time dedicated to science instruction was significantly influenced by external factors, such as whether science was a tested subject. Students with disabilities often face additional barriers, including being pulled out of science instruction for special education services, resulting in missed opportunities to engage in science. These findings highlight the need to address opportunity gaps in science instruction to ensure all students have meaningful access to quality science education.